KONSELING ISLAM DALAM MENANAMKAN NILAI-NILAI SPRITUAL PELAKU BULLYING - Faisal Akbar; Silvianetri Silvianetri (Universitas Islam Kalimantan Muhammad Arsyad Al-Banjari Banjarmasin, 2023)
Every human being is inseparable from mistakes and actions, so there is a need for Islamic counseling in the process of helping clients who need advice and motivation according to the teachings of Assunnah and the Koran, by instilling religious values that can be carried out by perpetrators of bullying. The purpose of this research is to find out how Islamic counseling in instilling the spiritual values of bullying. The type of this research is descriptive qualitative. Descriptive qualitative research is research to describe and strengthen predictions of a phenomenon that applies on the basis obtained in the field. The results in this study are that the importance of Islamic counseling in instilling the spiritual values of bullying perpetrators, by carrying out religious values, at least can help perpetrators carry out according to their nature as Islamic humans, because Islamic humans can follow the teachings and rules that have been established in Islam. Regarding bullying such as making fun of, ridiculing, hitting accidentally is an act that is prohibited by Islam. This is the importance of Islamic counseling in providing spiritual values.